RAF1 deficiency causes a lethal syndrome that underscores RTK signaling during embryogenesis - Samantha Wong; Yu Xuan Tan; Abigail Yi Ting Loh; Kiat Yi Tan; Hane Lee; Zainab Aziz; Stanley F Nelson; Engin Özkan; Hülya Kayserili; Nathalie Escande‐Beillard; Bruno Reversade (EMBO Molecular Medicine, 2023)
Abstract Somatic and germline gain‐of‐function point mutations in RAF, one of the first oncogenes to be discovered in humans, delineate a group of tumor‐prone syndromes known as the RASopathies. In this study, we document the first human phenotype resulting from the germline loss‐of‐function of the proto‐oncogene RAF1 (a.k.a. CRAF). In a consanguineous family, we uncovered a homozygous p.Thr543Met variant segregating with a neonatal lethal syndrome with cutaneous, craniofacial, cardiac, and limb anomalies. Structure‐based prediction and functional tests using human knock‐in cells showed that threonine 543 is essential to: (i) ensure RAF1's stability and phosphorylation, (ii) maintain its kinase activity toward substrates of the MAPK pathway, and (iii) protect from stress‐induced apoptosis mediated by ASK1. In Xenopus embryos, mutant RAF1T543M failed to phenocopy the effects of normal and overactive FGF/MAPK signaling, confirming its hypomorphic activity. Collectively, our data disclose the genetic and molecular etiology of a novel lethal syndrome with progeroid features, highlighting the importance of RTK signaling for human development and homeostasis.